2017
DOI: 10.1136/bmjopen-2016-013787
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of haemostatic dysfunction and bleeding in neonates with hypoxic–ischaemic encephalopathy

Abstract: ObjectiveEvaluate the relationship between initial haemostatic parameters and the frequency and severity of bleeding in neonates with hypoxic–ischaemic encephalopathy (HIE).DesignRetrospective observational cohort study.Setting2 academically affiliated level III neonatal intensive care units in Atlanta, Georgia.Participants98 neonates with moderate-to-severe HIE who underwent haemostatic testing within 12 hours of birth and were born from 1 January 2008 to 31 December 2013.Primary and secondary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
(28 reference statements)
3
19
0
Order By: Relevance
“…9 Based on the comparison between the hypoxic and healthy neonates in this study, a potentially hypocoagulable profile in hypoxic neonates was detected. This finding is consistent with the results of Pakvasa et al, 11 who measured PT, platelet count, and fibrinogen in neonates with moderate-to-severe HIE. Moreover, Suzuki and Morishita 20 found plasma levels of thrombin-antithrombin complexes, D-dimer, fibrin(ogen) degradation products, and soluble fibrin monomer complexes markedly higher in the umbilical cord blood of asphyxiated newborns than in healthy neonates and El Beshlawy et al 21 reported a marked decrease of antithrombin, protein C, and protein S in asphyxiated neonates, both noting high incidence of DIC in their study population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…9 Based on the comparison between the hypoxic and healthy neonates in this study, a potentially hypocoagulable profile in hypoxic neonates was detected. This finding is consistent with the results of Pakvasa et al, 11 who measured PT, platelet count, and fibrinogen in neonates with moderate-to-severe HIE. Moreover, Suzuki and Morishita 20 found plasma levels of thrombin-antithrombin complexes, D-dimer, fibrin(ogen) degradation products, and soluble fibrin monomer complexes markedly higher in the umbilical cord blood of asphyxiated newborns than in healthy neonates and El Beshlawy et al 21 reported a marked decrease of antithrombin, protein C, and protein S in asphyxiated neonates, both noting high incidence of DIC in their study population.…”
Section: Discussionsupporting
confidence: 93%
“…Few data exist in the literature on the study of hemostatic derangements using viscoelastic tests in asphyxiated neonates or in neonates with fetal distress. [9][10][11] We therefore aimed at investigating the hemostatic profile of neonates with perinatal hypoxia using TEM.…”
mentioning
confidence: 99%
“…Although moderate hypothermia can be therapeutic in term neonates following intrauterine hypoxemic/ischemic brain injury, hypothermia in premature neonates is associated with worse outcomes . In addition, hypoxemic/ischemic brain injury has been found to be independently associated with coagulopathy . Lester et al found that hypothermia in adult transfusion recipients was associated with increased blood product consumption and higher mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Pakvasa et al . (), there were notable haemostatic defects in patients with moderate to severe hypoxic ischaemic encephalopathy (HIE). This correlated with an increased risk of bleeding, although the authors did not assess survival.…”
Section: Discussionmentioning
confidence: 99%